Effects of the competition schedule in major-competition years on performance in major-competition: Evidence from speed- and power-type track and field events - Xiaolong Zhang; Xin Wei; Yao Yu; Tiantian Wang (PLoS ONE, 2026)
Objective This study aimed to examine the association between competition schedules in major-competition years (Olympic or World Championships years, M-Years) and performance in major-competition (M-Performance) among athletes in speed- and power-type track and field events. Methods This was a retrospective observational study involving athletes who competed in speed- and power-type track and field events at the World Athletics Championships or the Olympic Games between 1993 and 2019, yielding 14,584 valid observations. First, a two-step cluster analysis was conducted to identify typical M-Year competition schedules based on the annual total number of competitions and the proportions of performance states at each level. Next, baseline regression models were used to identify differences in M-Performance across competition-schedule types and to determine the “optimal competition schedule.” Finally, fixed-effects models were employed to explore the association between adjusting from a “suboptimal competition schedule” to the “optimal competition schedule” and M-Performance. Results Athletes’ competition schedules in M-Years were classified into three types: “major-event–focused,” “competition-oriented,” and “competition-as-training.” Among these, athletes under the “competition-oriented” schedule exhibited significantly better M-Performance than those under the other two schedules. Further analysis showed that adjustment from a “competition-as-training” schedule to a “competition-oriented” schedule was associated with higher M-Performance, whereas adjustment from a “major-event–focused” schedule to a “competition-oriented” schedule showed no similar association. Conclusions In M-Years, even the optimal competition schedule may not be suitable for all athletes, and its effectiveness may vary by athlete type. For “competition-as-training” athletes, adjusting toward a “competition-oriented” schedule may be associated with higher M-Performance. However, such adjustment may have limited benefits for “major-event–focused” athletes. To the best of our knowledge, this study is the first to conduct a large-scale empirical analysis of competition scheduling in major-competition years. The findings provide an empirical basis for future studies to further examine the causal relationship between competition-schedule adjustments and M-Performance, while also offering practical reference for athletes and coaching teams preparing for major events such as the Olympic Games and the World Athletics Championships.